(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Introduction: Exploring the taxonomic diversity of diatoms in the Varuna River unveils a fascinating realm with profound implications for forensic investigations. The intricate ecological web of these microscopic organisms offers a unique lens to scrutinize environmental dynamics, providing valuable insights crucial in forensic science for accurate analysis and interpretation. Aim: This study aims to analyze diatom populations in the Varuna River across Varanasi, Prayagraj, Bhadohi, and Jaunpur, focusing on their identification, quantification, distribution, and forensic relevance in drowning cases. Methodology: This qualitative experimental study investigates Diatom species variation along the Varuna